PERAN PETANI PEMANDU DALAM ADOPSI TEKNOLOGI ECO-RICE PADA PROGRAM BUILDING DISASTER AND CLIMATE CHANGE RESILIENCE (BDCCR) DI KABUPATEN PADANG PARIAMAN - , PUJI WAHYU MULYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to: (1) identify the level of the role of guiding farmers in Eco- Rice technology adoption, (2) analyze the level of Eco-Rice technology adoption by the farmers, and (3) analyze the factors that influence to the rate of adoption of Eco-Rice technology. The basic method used in the study was descriptive method with a quantitative approach. The research was conducted in Padang Pariaman, West Sumatera. Data were collected through observation, interviews and recording. The hugeholds samples of this research were 50 farmers participant of Field School Eco-Rice on FIELD-Bumi Ceria Program. The statistical method used in the study include Chi Square analysis and Gamma test. The research result showed: (1) the role of the guiding farmers high category, (2) the level of Eco-Rice tehcnology adoption by the Farmers is in low category, and (3) the factors that positively influence to the Eco-Rice technology adoption is the role of the guiding farmers. The higher role of the guiding farmer, will be the higher the level of Eco-rice adoption technology by the Farmers in the district of Padang Pariaman. Internal factors namely age, education, experiences, land of size, family income, and social status as well as external factors the nature of innovation do not significantly influence to adoption of Eco-Rice technology.